Supply chain and ICT issues of Estonia: Survey findings - Ain Kiisler; Tomi Solakivi; Olli-Pekka Hilmola (Netherlands, 2022)
Logistics and supply chain management are critical for economic sustainability. In this research, we aim to identify the most critical factors to logistics and supply chain performance for a small open economy by reporting survey results from Estonian manufacturing, trading and logistics service companies. By comparing survey results from 2012 and 2018, we also analyze how these critical factors may have changed during the last years. In the survey, the significance of competitiveness, functionality of logistics, and information and communication technologies (ICT) among others were included. The results indicate that the importance of factors such as purchasing, demand forecasting and operations planning have increased. Overall, purchasing and demand forecasting are considered more important than other factors. Surprisingly, logistics was considered less vital in 2018 than in 2012. Most of the current challenges in companies arise from demand management (forecasting and planning), increasing labour costs and regulatory changes. On ICT side change has been from traditional communications more towards digital, and especially using specific platforms (portals, intranet/extranet).
Knowledge-Based and Intelligent Information & Engineering Systems: Proceedings of the 24th International Conference KES2020